2019
DOI: 10.3390/v11060517
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Fowl Adenovirus Serotype 4 and Co-Infection by Immunosuppressive Viruses in Fowl with Hydropericardium Hepatitis Syndrome in Shandong Province, China

Abstract: Fowl adenovirus serotype 4 (FAdV-4) is the pathogenic agent of hydropericardium hepatitis syndrome (HHS) in chickens and ducks, which has caused huge economic losses for the Chinese poultry industry since 2015. In order to objectively determine the prevalence and co-infection status of the virus in Shandong province in China, we analyzed a total of 679 clinical cases of chickens and ducks from 36 farms in the province. The results showed that the FAdV-4 infection rate was 65.2% (443/679), and the rate in breed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Novel antigenic variant IBDV and FAdV-4 have both occurred frequently in China, recently causing huge economic losses [ 6 , 11 ], and FAdV co-infection with IBDV in chickens has been reported [ 16 , 18 ]. In this study, we developed a co-infection model in SPF chickens using the novel variant IBDV strain ZD-2018-1 and the FAdV-4 isolate HB1501 to explore the interaction between these infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel antigenic variant IBDV and FAdV-4 have both occurred frequently in China, recently causing huge economic losses [ 6 , 11 ], and FAdV co-infection with IBDV in chickens has been reported [ 16 , 18 ]. In this study, we developed a co-infection model in SPF chickens using the novel variant IBDV strain ZD-2018-1 and the FAdV-4 isolate HB1501 to explore the interaction between these infections.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2015, FAdV-4 has occurred in several provinces in China [ 11 , 13 15 ] and attracted much attention in the poultry industry. Furthermore, some studies have reported that poultry can become coinfected with FAdV and other avian diseases, such as avian influenza virus (AIV), IBDV, and chicken infectious anemia virus (CIAV) [ 16 19 ]. FAdV co-infection with other infectious agents has become a non-negligible issue.…”
Section: Introductionmentioning
confidence: 99%
“…We received several papers on veterinary viruses. Yu et al [19] present data on the prevalence and co-infection of fowl adenovirus. Meng et al [20] identify and characterize a novel fowl adenovirus and perform an immunoprotective evaluation of an inactivated FAdV-4 vaccine.…”
mentioning
confidence: 99%
“…It has been reported that severe HEV infections have occurred in several provinces in China since 2016 [10,3,11]. In recent years, outbreaks of BLS and HS syndrome in chicken ocks have gradually increased in Shandong province [10,12]. In order to investigate the causes of BLS and HS syndrome, and the epidemic characteristics of avian HEV in Shandong province, 18 cases of hepatomegaly and splenomegaly were collected for histopathology examination and pathogen detection, including HEV, MDV, FAdV, ALV, CIAV, and REV.…”
Section: Discussionmentioning
confidence: 99%